Eliminating Violence against Women in Pacific through Multi-Track Diplomacy - Sherly Mega Putri; Elisabeth Adyiningtyas Satya Dewi (Jurnal Ilmiah Hubungan Internasional, 2018)
Humanitarian issue that often raised as a problem for developing countries, is often likely linked to gender issue. Having labeled as a region with the highest violence data prevalence, Pacific Islands countries possess assorted factors that tolerates the practice of gender dominance and discrimination amongst their societies. Responding this phenomenon, the governments in Pacific Islands countries are oftentimes receiving assistance from other international relations actors, in which one of them is UN Women. With the support from Australian government, this UN body assist numerous institutions from various level in making the effort to eliminate violence against women as the most protrude form of gender based discrimination in Pacific. Involvement of other parties from diverse groups indicates the relations between actors of Multi-Track Diplomacy with the program initiated by UN Women. Using theory of Multi-Track Diplomacy and concept of Gender-Based Violence, this research identifies the participation and contribution made by a total of nine tracks in responding to violence against women issue in the Pacific. Such response itself is one of the world peace endeavors, which is also the ultimate purpose of Multi-Track Diplomacy. Result of this response shaped in their participation and contribution within variety of programs under Pacific Fund. Keywords: Pacific, gender equality, foreign aids, Multi-Track Diplomacy, peacemaking.